An electroporation device with microbead-enhanced electric field for bacterial inactivation - Pudasaini, Sanam (2020)
This paper presents an electroporation device with high bacterial inactivation performance (~4.75 log removal). Inside the device, insulating silica microbeads are densely packed between two mesh electrodes that enable enhancement of the local electric field strength, allowing improved electroporation of bacterial cells. The inactivation performance of the device is evaluated using two model bacteria, including one Gram-positive bacterium (Enterococcus faecalis) and one Gram-negative bacterium (Escherichia coli) under various applied voltages. More than 4.5 log removal of bacteria is obtained for the applied electric field strength of 2 kV/cm at a flowrate of 4 mL/min. The effect of microbeads on the inactivation performance is assessed by comparing the performance of the microbead device with that of the device having no microbeads under same operating conditions. The comparison results show that only 0.57 log removal is achieved for the device having no microbeads—eightfold lower than for the device with microbeads.